2017
DOI: 10.1159/000464116
|View full text |Cite
|
Sign up to set email alerts
|

Decidualization is Impaired in Endometrial Stromal Cells from Uterine Rudiments in Mayer-Rokitansky-Küster-Hauser Syndrome

Abstract: Background/Aims: Uterine rudiments from patients with Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) contain all tissues typically found in the uterus. Endometrium from the rudiments predominantly exhibits basalis-like features, and endometrial proliferative capacity in patients’ epithelium and stroma is significantly lower. Methods: This single-center, prospective study conducted at a major German university hospital compared in-vitro decidualization in cultured ESCs from MRKHS patients and hysterectomy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
6
16
2
Order By: Relevance
“…The analogous analysis for type 2 was omitted due to the highly skewed sample distribution with respect to cycle stages. Together, these analyses are in line with previous reports that the endometrium of MRKH patients does not respond correctly to cycle hormones ( Ludwig, 1998a , b ; Rall et al, 2013 ; Brucker et al, 2017 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The analogous analysis for type 2 was omitted due to the highly skewed sample distribution with respect to cycle stages. Together, these analyses are in line with previous reports that the endometrium of MRKH patients does not respond correctly to cycle hormones ( Ludwig, 1998a , b ; Rall et al, 2013 ; Brucker et al, 2017 ).…”
Section: Resultssupporting
confidence: 91%
“…Instead, the expression of most genes remained in the proliferative phase although the hormonal profiles indicate patients were in the secretory phase. This finding agrees with previous studies that describe lacking responsiveness of the endometrium to hormones in MRKH patients ( Ludwig, 1998a , b ; Rall et al, 2013 ; Brucker et al, 2017 ). The transcriptome data we provide now offer the opportunity to trace the phenomenon to individual genes and pathways and examine co-occurring effects.…”
Section: Discussionsupporting
confidence: 93%
“…Instead, the expression of most genes remained in the proliferative phase although the hormonal profiles indicate patients were in the secretory phase. This finding agrees with previous studies that describe lacking responsiveness of the endometrium to hormones in MRKH patients (15)(16)(17)(18). The transcriptome data we provide now offer the opportunity to trace the phenomenon to individual genes and pathways and examine co-occurring effects.…”
Section: Discussionsupporting
confidence: 91%
“…The analogous analysis for type 2 was omitted due to the highly skewed sample distribution with respect to cycle stages. Together, these analyses are in line with previous reports that the endometrium of MRKH patients does not respond correctly to cycle hormones (15)(16)(17)(18).…”
Section: Endometrial Gene Expression Changes During the Menstrual Cycsupporting
confidence: 91%
“…It contains a 3-unit tetratricopeptide repeat structural motif connected to a domain that mediates enzymatic function and peptidyl prolyl isomerase activity. FKBP51 interacts with glucocorticoid, androgen, estrogen, progestin and mineralocorticoid receptors ( 2 7 ) through a number of components of the molecular chaperone machinery, including heat shock protein 90. FKBP51 has been identified to be upregulated or downregulated in multiple types of cancer and to be associated with cell motility and invasion, for instance, Leach et al ( 8 ) identified that FKBP51 is increased in prostate cancer cells compared with normal prostate epithelial cells and improves the ability of stromal androgen receptor to predict prostate cancer-specific mortality.…”
Section: Introductionmentioning
confidence: 99%